Overexpression of DNA polymerase β in cell results in a mutator phenotype and a decreased sensitivity to anticancer drugs - Canitrot, Yvan (The National Academy of Sciences, 1998)
DNA polymerase β (pol β) is the most error prone of all known eukaryotic DNA polymerases tested in vitro. Here, we show that cells overexpressing pol β cDNA have acquired a spontaneous mutator phenotype. By measuring the appearance of mutational events using three independent assays, we found that genetic instability increased in the cell lines that overexpressed pol β. In addition, these cells displayed a decreased sensitivity to cancer chemotherapeutic, bifunctional, DNA-damaging agents such as cisplatin, melphalan, and mechlorethamine, resulting in enhanced mutagenesis compared with control cells. By using cell-free extracts and modified DNA substrates, we present data in support of error-prone translesion replication as one of the key determinants of tolerance phenotype. These results have implications for the potential role of pol β overexpression in cancer predisposition and tumor progression during chemotherapy.